Surfing amongst Oil-Tankers: Connecting Emerging Research Fields to the Current International Landscape. (January 2017) - Charrier, Bénédicte; Coates, Juliet C.; Stavridou, Ioanna
Abstract : The COST Action Phycomorph (FA1406) was initiated in 2015 from a handful of academic researchers, and now joins together 19 European countries and nine international partners. Phycomorph's goal is to coordinate and develop research on developmental biology in macroalgae. This is an ambitious project, as the related scientific community is small, the concepts are complex, and there is currently limited knowledge of these organisms and there are few technologies to study them. Here we report the first step in achieving this enterprise, the creation of the Phycomorph network. We share the associated strengths, pitfalls, and prospects for setting up the network in the hope that this might guide similar efforts in other fields.